APLIKASI GAME MARIO BROSS VERSI HARD PLAYER UNTUK WINDOWS - JEFRY ANDREANTONI .D, 13.01.55.0032 (Information Technology and Telematics, 2017)
Jefry Andreantoni .D, Eko Nur Wahyudi S.Kom, M.CsAbstract  –  Game  as  entertainment  has envolved with very rapidly along the development of technology.  Along  with  the  development  also  more and more. Example Game Mario still original or not changed very easy to be missed and can be passed easily dan fast. Create  Game  mario  with  new  obstacle,  need more time,patience, accuracy, for trap make player must remembertrap layout.Keywords : Game, 2- Dimention, Mario, blockage